Concepções de docentes de biologia da grande Aracaju sobre corpo - Lima, Edenilse Batista (2013)
The teaching of topics related to health has been a challenge for education, with regard to the possibility of ensuring effective learning and transforming attitudes and lifestyles. A preventive measure is to promote health awareness of their own bodies and their own sexuality that is embedded in it. Beyond the issues of training, knowledge of one´s own body can be a key factor in building the physical well-being, mental and social conditions. Therefore, this paper aims at identifying and describing conceptions of teachers of Biology Aracaju Grande on the body and the possible effects of these conceptions for pedagogical practice. Seeking to meet these objectives this work was conducted by a qualitative approach. The collection of information was made using the technique of semi-structured individual interviews. According to the results the teachers possess a design facing a symbolic body and a machine body. The latter, probably because the area of teacher training as undergraduates while the body is presented to them in a fragmented, disconnected from any context identity, whether sociocultural, ethnic, sexual or gender. The symbolic body is divided into several other bodies that are interrelated psychological body, erotic, Socioeconomic and aesthetics. Remember that the body is a building biopsicosocioeconomicocultural and therefore, understand, in a way, these conceptions. We teachers need to sensitize the students with respect to the appreciation of diversity that exists in the world body and the questioning of standardizations pertaining mainly to the body and sexuality